Eavesdropping: A Cyber Security Challenge in the Era of Internet of Things (IoT) - Rudy Agus Gemilang Gultom, Tri Legionosuko, Romie Octavianus Bura, Susilo Adi Putro (International Journal of Advanced Science and Technology, 2020)
In the time of Internet of Things (IoT), data or information seek motion on the Internet is one of the poor impacts of interconnection of Internet customers (get interconnected) and the simplicity of data sharing on the net. The misplaced of touchy statistics or statistics or giant archives ought to be possible in light of the truth that there may be no ok digital protection. Thusly, clients should aware about facts protection via Internet get to.